Design of a Portable Paddy Dehusking Machine - Shayfull Zambree, Abd. Rahim; Mohd Fathullah, Ghazli@Ghazali; Mohd Azaman, Md Deros (Universiti Teknikal Malaysia Melaka (UTeM), 2011)
International Conference on Design & Concurrent Engineering 2010 (iDECON 2010) organized by Universiti Teknikal Malaysia (UTeM) Melaka, 20th - 21st September 2010 at Avillion Legacy Hotel, Melaka, Malaysia.